Serum levels of B-cell activating factor of the TNF family (BAFF) correlate with anti-Jo-1 autoantibodies levels and disease activity in patients with anti-Jo-1positive polymyositis and dermatomyositis - Kryštůfková, Olga; Hulejová, Hana; Mann, Heřman F; Pecha, Ondřej; Půtová, Ivana; Ekholm, Louise; Lundberg, Ingrid E; Vencovský, Jiří (Arthritis research & therapy, 2018)
BACKGROUND: B-cell activating factor of the tumour necrosis factor family (BAFF) plays a role in autoantibody production and is elevated in dermatomyositis (DM) and anti-Jo-1-positive polymyositis (PM). We investigated the inter-relationships between serum levels of BAFF, anti-Jo-1 autoantibodies, and disease activity. METHODS: Serum levels of BAFF and anti-Jo-1 antibodies measured by enzyme-linked immunosorbent assay (ELISA) were compared to levels of myoglobin, creatine kinase (CK), aminotransferases (alanine (ALT) and aspartate (AST)), C-reactive protein (CRP), and disease activity assessed by the Myositis Disease Activity Assessment Tool in 63 anti-Jo-1 antibody-positive DM/PM patients. Serial serum samples collected at 2 (46 cases) and 3-5 time points (23 cases) were included. Relationships between BAFF, anti-Jo-1, disease activity, CRP, and their longitudinal changes were evaluated using correlation analysis, multiple regression (MR), path analysis (PA), and hierarchical linear models (HLM). RESULTS: Cross-sectional assessment demonstrated significant correlations between the levels of BAFF and anti-Jo-1 antibodies which were associated with levels of CK, myoglobin, AST, and CRP, as well as multivariate associations between BAFF, anti-Jo-1 antibodies, and CK levels. PA revealed direct effects of anti-Jo-1 antibodies on CK (β = 0.41) and both direct (β = 0.42) and indirect (through anti-Jo-1 antibodies; β = 0.17) effects of BAFF on CK. Changes in levels of both BAFF and anti-Jo-1 between two time points (Δ) were associated with Δmyoglobin and Δaminotransferases and changes of BAFF correlated with ΔCK, Δcutaneous, Δmuscle, Δglobal, and Δskeletal disease activities. The longitudinal analysis showed a high intra-individual variability of serum levels of BAFF over time (97%) which could predict 79% of the variance in anti-Jo-1 levels. The anti-Jo-1 variability was explained by inter-individual differences (68%). The close longitudinal relationship between levels of BAFF, anti-Jo-1, and disease activity was supported by high proportions of their variance explained with serum levels of CK and CRP or pulmonary and muscle activities. CONCLUSION: Our findings of associations between levels of BAFF and anti-Jo-1 antibodies in serum and myositis activity suggest a role of this cytokine in disease-specific autoantibody production as part of disease mechanisms, and support BAFF as a potential target for intervention in anti-Jo-1-positive myositis patients.
Keywords: B-Cell Activating Factor; ILD; Humans; dermatomyozitida; Longitudinal Studies; Myositis; histidin-tRNA-ligasa; lidé středního věku; faktor aktivující B-buňky; antinukleární protilátky; Female; Aged; BAFF; dospělí; senioři; lidé; Dermatomyositis; Adult; Antibodies, Antinuclear; ženské pohlaví; longitudinální studie; Male; Middle Aged; Cross-Sectional Studies; Anti-Jo-1 autoantibodies; Histidine-tRNA Ligase; mužské pohlaví; průřezové studie